Parks, Recreation, and Public Health Collaborative - Judy Kruger (SAGE Publishing, 2008)
The primary goal of many park and recreation agencies is to provide resources and programs that improve quality of life for the community. Increasing physical activity is one aspect of this agenda. Promoting physical activity is a public health goal; however, increasing population-level physical activity will require access to places for physical activity (e.g. parks). Practitioners and policy makers need more information to document the roles that parks and recreation facilities play to promote physical activity and contribute to public health. A working group of approximately 20 professionals experienced in data collection came together to discuss the needs for better surveillance and measurement instruments in the fields of parks, recreation, and public health. The working group made two major recommendations: (1) the need for collaborative research and data sharing, and (2) the need for surveillance measures to demonstrate the amount of health-related physical activity acquired in the park setting.